The Revitalization of Popular Theatre Forms in Contemporary Performance: The Case of Post-Soviet Lithuanian Theatre - Mažeikienė, Rūta (Nordic Theatre Studies, 2018)
The article examines the use of historical popular theatre forms in contemporary performance and analyses how historical popular theatre forms are revitalized in contemporary theatre. The first part of the article addresses the phenomena of popular theatre in general. Referring to the insights on this topic by such theatre scholars as D. Mayer (1972), P. Pavis (1998), T. Grammatas (2013) the article addresses the problem of the definition of popular theatre and discusses what are the major characteristics that make the forms of popular theatre into the source of creative renewal and artistic inspiration. The second part of the article analyses how historical popular theatre practices (such as pantomime, mime, puppetry or shadow plays) have been used by post-Soviet Lithuanian theatre artists – namely, director Gintaras Varnas at Šėpa theatre and director Vega Vaičiūnaitė at Miraklis theatre – as a stimulus to renew theatrical language and to foster new relationship with theatre audiences. The examples of both companies demonstrate that in spite of the conventional genre restrictions, the historical forms of popular theatre are not treated as an unquestionable museum relic, but rather as a means to create a live and immediate contact with a contemporary audience through universal historical forms.